The influence of room spaciousness on investigative interviews. (30th June 2019) - Hoogesteyn, Katherine; Meijer, Ewout; Vrij, Aldert
Abstract : Purpose: The quality of information obtained from investigative interviews largely relies on the quality of communication between the interviewee and interviewer. One aspect of the communication process that has yet to be well examined is the environment in which the interviews take place. The present study examined the influence of physical spaciousness, manipulated as room size and interpersonal sitting distance between interviewer and interviewee on the disclosure of crime‐related information, as well as perceptions of rapport and overall interview experience. Methods: Participants engaged in a virtual reality scenario depicting a crime and were interviewed as suspects in either a larger or smaller room, at a closer or larger distance. Results: Results showed no links between room size and sitting distance on disclosure rates. However, an exploratory analysis did reveal that participants interviewed in the larger room reported more positive interview experience in terms of spaciousness, and consequently higher perceptions of rapport, compared to those interviewed in the small room. Conclusions: We found evidence against an influence of room size and interpersonal distance on disclosure. Still, our study does provide initial evidence that manipulating room size in an interview context could positively impact rapport‐building.